9a(-7a+4)=

Simple and best practice solution for 9a(-7a+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9a(-7a+4)= equation:


Simplifying
9a(-7a + 4) = 0

Reorder the terms:
9a(4 + -7a) = 0
(4 * 9a + -7a * 9a) = 0
(36a + -63a2) = 0

Solving
36a + -63a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '9a'.
9a(4 + -7a) = 0

Ignore the factor 9.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(4 + -7a)' equal to zero and attempt to solve: Simplifying 4 + -7a = 0 Solving 4 + -7a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7a = 0 + -4 -7a = 0 + -4 Combine like terms: 0 + -4 = -4 -7a = -4 Divide each side by '-7'. a = 0.5714285714 Simplifying a = 0.5714285714

Solution

a = {0, 0.5714285714}

See similar equations:

| 5y^4+3y^4= | | 3u-10=14 | | 4+(x-5)=2(3-x) | | 4x^2-28x+c= | | Z+20=6 | | (Xy^2)(x^2+3xy+9)=0 | | 2x^8+6x^8= | | 2(x+6)x^2=90 | | 21x^2y+2xy-8=0 | | 3(x-2)=5(2+3) | | h+h+4=218 | | y=x^5+6x+8 | | 14(y-7)+12y=16-70 | | 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 | | 28u^2-27u-10=0 | | .06(z-300)+.05z=.70z-205 | | 25+30=35+20 | | 0=x^4-4x^3-24x^2+20x+7 | | 5z(x-6y)+7(x-6y)=0 | | 3w-6=20 | | y=abs(4-x) |

Equations solver categories